Cloud Kitchen – Revolutionizing the Restaurant Industry - Vishal Pandey Dr. Lokeshver Singh Jodhana (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
The restaurant industry is undergoing a transformative shift with the emergence of cloud kitchens, a concept that is revolutionizing traditional business models. Cloud kitchens leverage technological advancements and innovative operational practices to redefine the way food is prepared, delivered, and consumed. This study explores the disruptive impact of cloud kitchens on the restaurant industry, emphasizing their potential to create new opportunities, address modern challenges, and reshape industry dynamics. The core objective of this study is to analyze how cloud kitchens are redefining the restaurant sector, investigating their innovative business models and practices. It delves into the ways cloud kitchens are introducing fresh perspectives, streamlining processes, and influencing consumer behavior. Moreover, the research evaluates the comparative effectiveness of various cloud kitchen business models in driving innovation and reshaping industry norms. Drawing on concepts such as technological innovation, digital transformation, and adaptive business strategies, this research employs a mixed-methods approach, combining content analysis and interviews.